2009
DOI: 10.1097/rct.0b013e318187fed0
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Infarct Size Assessed With 0.1 mmol/kg of Gadobenate Dimeglumine Correlates With That Assessed With 0.2 mmol/kg of Gadopentetate Dimeglumine

Abstract: Objective To determine myocardial infarct (MI) size during cardiovascular magnetic resonance (CMR) at 1.5 Tesla using 0.1 mmol/kg bodyweight of gadobenate dimeglumine (Gd-BOPTA) and 0.2 mmol/kg bodyweight of gadopentetate dimeglumine (Gd-DTPA). Methods Twenty participants (16 men, 4 women), aged 58 ± 12 years, with a prior chronic MI were imaged in a cross-over design. Participants received 0.2 mmol/kg bodyweight of Gd-DTPA, and 0.1 mmol/kg bodyweight of Gd-BOPTA on 2 occasions separated by 3 to 7 days Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Previous studies in humans by Huang et al have demonstrated the feasibility of half‐dose imaging using gadobenate dimeglumine at 3 T vs. gadopentetate dimeglumine at 1.5 T in the setting of brain neoplasia . Analogous findings have been demonstrated in other applications . The present study further examines the ability to reduce gadolinium chelate dosage with gadobenate dimeglumine, hypothesizing that the near double r1 relaxivity of gadobenate dimeglumine at both 1.5 and 3 T relative to gadopentetate dimeglumine could allow for a halving of doses with the former while preserving lesion enhancement.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies in humans by Huang et al have demonstrated the feasibility of half‐dose imaging using gadobenate dimeglumine at 3 T vs. gadopentetate dimeglumine at 1.5 T in the setting of brain neoplasia . Analogous findings have been demonstrated in other applications . The present study further examines the ability to reduce gadolinium chelate dosage with gadobenate dimeglumine, hypothesizing that the near double r1 relaxivity of gadobenate dimeglumine at both 1.5 and 3 T relative to gadopentetate dimeglumine could allow for a halving of doses with the former while preserving lesion enhancement.…”
Section: Discussionsupporting
confidence: 69%
“…[3,7] Due to a higher relaxivity [13] related to protein binding, some publications report gadobenate dimeglumine (Gd-BOPTA) at a lower dose of 0.1 mmol/kg for CMR [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…As previously reported by other authors [15][16][17][18]20], a gadobenate dimeglumine dose of 0.1 mmol/kg BW generally provides an excellent image quality for determinations of IM size and volume.…”
Section: Discussionmentioning
confidence: 62%
“…Comparative CMR studies, both inter-individually [15,16] and intra-individually [17,18], have similarly shown that a dose of 0.1 mmol/kg BW Gd-BOPTA is equivalent to a double 0.2 mmol/kg BW dose of Gd-DTPA in terms of both scar depiction and quantification of necrotic tissue.…”
Section: Introductionmentioning
confidence: 92%